High growth entrepreneurs, public policies and economic growth - Erik Stam; Kashifa Suddle; S. Jolanda A. Hessels; André J. van Stel (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2007)
This paper investigates whether the presence of ambitious entrepreneurs is a more important determinant of national economic growth than entrepreneurial activity in general. We use data from the Global Entrepreneurship Monitor to test the extent to which high growth ambitions of entrepreneurs affect GDP growth for a sample of 36 countries. Our results suggest that ambitious entrepreneurship contributes more strongly to macro-economic growth than entrepreneurial activity in general. We find a particularly strong effect of high-expectation entrepreneurship for transition countries. These results are interpreted in light of the ongoing debate about public policies designed to stimulate high growth start-ups.
Keywords: L16; L21; M13; O11; O40; O57; 330; entrepreneurial activity; high growth entrepreneurs; growth ambitions; high growth start-ups; public policy; economic growth; Unternehmer; Wirtschaftswachstum; Unternehmensgründung; Unternehmenswachstum; Persönlichkeitspsychologie; Welt; Transformationsstaaten